Self-Empowerment of The Elderly in Depression Reduction Through Laughter Therapy - Utari, Dewi; Hidayati, Rizqi Wahyu; Sugiyono, Sugiyono; Pamungkas, Dewi Retno (Wikrama Parahita : Jurnal Pengabdian Masyarakat, 2025)
The ageing process brings many physical, psychological, social and spiritual changes to older people. Psychological and social changes include a different work rhythm due to retirement, loss of friends and partners, fear and anxiety about death, loneliness, etc. This leads to the risk of anxiety and depression in older people. Depression or psychosocial disorders affect older people physically and might reduce their quality of life. Therefore, in order to prevent and overcome these problems, an intervention is needed through laughter therapy. This community service activity consists of five stages, starting from problem identification to program sustainability follow-up. The participants of this activity were 37 elderly members of the hypertension class of Kalasan Puskesmas Area. The activity method consists of 5 stages. The elderly are empowered to practice laughter therapy, which is evaluated using the Geriatric Depression Scale (GDS) questionnaire. The results of the activity showed that the elderly had the ability to perform the therapy independently and that the results of the activity were able to reduce depression levels. In the pre-test assessment, 14.3% of respondents in the middle-aged group exhibited a severe level of depression. Meanwhile, the elderly and young-old groups demonstrated moderate levels of depression, with prevalence rates of 21.1% and 27.3%, respectively. Post-test findings indicated a positive shift across all three groups, with a reduction in depression severity. The proportion of individuals experiencing moderate depression decreased to 14.3% in the middle-aged group, 5.3% in the elderly group, and 9.1% in the young-old group.